The intracoronary wires hand-in-hand technique for uncrossable bilateral microcatheters in CTO lesions: a single-center case series - Huan, Wang; Genrui, Chen; Youhu, Chen; Xiaolin, Lei; Peng, Han; Yamin, Zhang; Li, Yang; Kun, Lian; Chengxiang, Li; Haokao, Gao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe tip-in and rendezvous techniques are alternative strategies for antegrade conversion when the retrograde microcatheter (MC) cannot cross the chronic total occlusion (CTO) lesion. However, subsequent antegrade MC failure to cross the CTO lesion may increase the failure rate of the CTO procedure.ObjectivesWe sought to evaluate the efficacy of the intracoronary wires hand-in-hand (WHIH) technique in this scenario for achieving complete antegrade CTO recanalization.MethodFrom September 2023 to December 2024, 14 CTO patients were applied the WHIH technique. The main process of the WHIH technique involves keeping the antegrade and retrograde MCs in close proximity along the retrograde wire, then advancing both wires forward and backward in a hand-in-hand manner along the path created by the retrograde wire until the antegrade wire crosses the CTO lesion. Device success was defined as the achievement of antegrade wire crossing the CTO into the distal vessel after the WHIH technique.ResultsThe WHIH success was achieved in all cases. The mean age of the patients was 61.2 ± 12.4 years, and 85.7% of patients were male. The median CTO lesion length was 27.6 mm (range: 7.1–87.3 mm), and the mean J-CTO score was 2.5 ± 0.9. The retrograde approach was predetermined as the first choice in six cases (42.9%), and in eight cases (57.1%) was promptly adopted after the initial antegrade approach failed. Eight cases (57.1%) were accessed through septal collaterals, whereas the remaining six cases (42.9%) via epicardial channels and four of them used ipsilateral epicardial channels. All patients were treated with the tip-in technique, and the median length between two MCs was 4.5 mm (range: 2–20 mm). The WHIH success was achieved in all cases. In-hospital major adverse cardiovascular (MACE) events were not observed.ConclusionThis intracoronary wires hand-in-hand technique safely and effectively enables antegrade conversion from a retrograde approach, which may serve as a last-resort technique for antegrade access.